Human Resource Education Management in Efforts to Foster Interest in Entrepreneurship through Digital Media in Masawah Village - Nurhidayat Nurhidayat; Irpan Ilmi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
This study aims to analyze how human resource management (HRM) education can be optimized to increase entrepreneurial interest through digital media in Masawah Village. The main issues in this study are the low interest in entrepreneurship through digital media and the suboptimal human resource management in Masawah Village. This study uses a qualitative approach with a case study method, data collection techniques through interviews, observation, and documentation with prominent figures in Masawah Village. The research results show that there have been various training initiatives, but HR practices are still carried out informally and have not been fully documented, and are not supported by structured leadership, strong institutions, cross-agency coordination, and a performance-based evaluation system. This study contributes to the limited human resource education management in villages, by highlighting the importance of systematically implementing management functions in building a digital entrepreneurship ecosystem in rural areas, which distinguishes it from previous studies that generally focus on urban contexts or formal institutions.